Consumer Acceptance Of Technology In The Financial Service Industry - Leong, Peih Shine (2006)
This research investigates the extent of consumer acceptance on the electronic banking implementation by using a modified Technology Acceptance Model (TAM). The scope of the research is confined to the online banking acceptance in Malaysia.